Beetles as Model Organisms in Physiological, Biomedical and Environmental Studies – A Review - Adamski, Zbigniew; Bufo, Sabino A.; Chowański, Szymon; Falabella, Patrizia; Lubawy, Jan; Marciniak, Paweł; Pacholska-Bogalska, Joanna; Salvia, Rosanna; Scrano, Laura; Słocińska, Małgorzata; Spochacz, Marta; Szymczak, Monika; et al. (Frontiers in Physiology, 2019)
Model organisms are often used in biological, medical and environmental research. Among insects, Drosophila melanogaster, Galleria mellonella, Apis mellifera, Bombyx mori, Periplaneta americana, and Locusta migratoria are often used. However, new model organisms still appear. In recent years, an increasing number of insect species has been suggested as model organisms in life sciences research due to their worldwide distribution and environmental significance, the possibility of extrapolating research studies to vertebrates and the relatively low cost of rearing. Beetles are the largest insect order, with their representative – Tribolium castaneum – being the first species with a completely sequenced genome, and seem to be emerging as new potential candidates for model organisms in various studies. Apart from T. castaneum, additional species representing various Coleoptera families, such as Nicrophorus vespilloides, Leptinotarsa decemlineata, Coccinella septempunctata, Poecilus cupreus, Tenebrio molitor and many others, have been used. They are increasingly often included in two major research aspects: biomedical and environmental studies. Biomedical studies focus mainly on unraveling mechanisms of basic life processes, such as feeding, neurotransmission or activity of the immune system, as well as on elucidating the mechanism of different diseases (neurodegenerative, cardiovascular, metabolic, or immunological) using beetles as models. Furthermore, pharmacological bioassays for testing novel biologically active substances in beetles have also been developed. It should be emphasized that beetles are a source of compounds with potential antimicrobial and anticancer activity. Environmental-based studies focus mainly on the development and testing of new potential pesticides of both chemical and natural origin. Additionally, beetles are used as food or for their valuable supplements. Different beetle families are also used as bioindicators. Another important research area using beetles as models is behavioral ecology studies, for instance, parental care. In this paper, we review the current knowledge regarding beetles as model organisms and their practical application in various fields of life science.